The Characteristic of Calcium Fortified Fish Keropok from Belida Fish Bone - Indrati Kusumaningrum; Andi Noor Asikin (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
AbstractBelida (Chitala sp.) bone is one of the waste from amplang processing which not treated properlyyet until now especially in East Kalimantan. One type of the usage of this waste is processed to fish bonepowder as calcium source which can be added to various food formulations such as keropok. The aim ofthis study was to determine the chemical characteristics of belida fishbone powder added keropok Observedparameters in this study were moisture content, ash content, protein content, fat content, calcium content,phosphor content and whiteness. The method applied the experimental design was Completely RandomizedDesign with five treatments of 0% (K0), 5% (K1), 10% (K2), 15% (K3) dand 20% (K4) fishbone powderaddition with three replications to each treatments. The results showed that the addition of belida bonepowder hadn’t significant effect to moisture of fortified keropok while had significant effect on ash, protein,fat, calcium, phosphor content and whitness. The higher addition of fishbone powder increasing the value ofash, calcium, phosphor and whiteness but decreasing protein and fat content of fortifief keropok. The resultshowed that K3 was the best treatment with 5.64% calcium content.